2022
DOI: 10.3390/plants11040559
|View full text |Cite
|
Sign up to set email alerts
|

Water Stress Alters Morphophysiological, Grain Quality and Vegetation Indices of Soybean Cultivars

Abstract: Rainfall is among the climatic factors that most affect production, as in the Brazilian Cerrado. Non-destructive and automated phenotyping methods are fast and efficient for genotype selection. The objective of this work was to evaluate, under field conditions, the morphophysiological changes, yield, and grain quality of soybean (Glycine max L. Merrill) under water stress in the Brazilian Cerrado. The plots comprised six soybean cultivars and the subplots of four water regimes, corresponding to 31, 44, 64 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
2
12
0
Order By: Relevance
“…Seed oil content decreased under water stress in brown-seeded families. Previous studies found a negative correlation between oil and protein content in soybean seeds under water stress conditions that can also be explained by the competition of synthesis pathways by carbon skeletons, changes in accumulation, and the distribution of nutrients [21]. Similarly, in this study, the amount of fiber and fiber components such as ADF, NDF, CEL, HCEL, and lignin in seeds increased due to water stress, but it was more in brown-seeded genotypes.…”
Section: Association Of Brown Seed Color With the Amount Of Protein F...supporting
confidence: 71%
See 2 more Smart Citations
“…Seed oil content decreased under water stress in brown-seeded families. Previous studies found a negative correlation between oil and protein content in soybean seeds under water stress conditions that can also be explained by the competition of synthesis pathways by carbon skeletons, changes in accumulation, and the distribution of nutrients [21]. Similarly, in this study, the amount of fiber and fiber components such as ADF, NDF, CEL, HCEL, and lignin in seeds increased due to water stress, but it was more in brown-seeded genotypes.…”
Section: Association Of Brown Seed Color With the Amount Of Protein F...supporting
confidence: 71%
“…In the present study, in most families with brown seeds, water stress increased the amount of protein and amino acids more than the yellowseeded ones. Foroud et al [25] and Tavares et al [21] also observed an increasing amount and quality of protein under water deficit conditions in other oil seed crops such as soybean. When plants are stressed, they usually accumulate protein and amino acids.…”
Section: Association Of Brown Seed Color With the Amount Of Protein F...mentioning
confidence: 92%
See 1 more Smart Citation
“…Soybean culture is sensitive to water deficit, especially during the period of vegetative growth and development [37][38][39]; thus, it is possible to have a significant reduction in the leaf surface and even the abortion of flowers [40][41][42], a lower assimilation of nutrients [43], a smaller number of pods [7,40], as well as a 14-32% reduction in grain size (as observed by Souza et al in 1997) [44], all of which led to a decrease in yield, as also revealed by the data obtained by Van Heerden and Krüger in 2002 [45]. Excess soil water is equally harmful, limiting the yield potential, as observed by Santos and Carlesso in 1998 [46] and Lobato et al in 2008 [47], who carried out various experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Most VIs are ratios or linear combinations of spectral reflectance in two or more wavelength bands [ 39 ] that can be obtained from HSI [ 37 , 40 ]. Consisting of a straightforward transformation of spectral bands, VIs are estimated without bias or presumptions about land cover class, soil type, or climate conditions—enabling the observations of seasonal and long-term changes in a vegetation’s structural, phenological, and biophysical characteristics [ 41 , 42 , 43 ]. VIs have proven to be a valuable tool for monitoring plant health and productivity, and they are widely applied in fields such as agriculture, forestry, and ecology.…”
Section: Introductionmentioning
confidence: 99%